The Role of Accounting Information Systems in Strengthening Organizational Resilience: An Empirical Investigation Using the SEM-ANN Approach - Al-Matari A.S.; Al-Sharafi M.A.; Hajar M.A. (Springer Science and Business Media Deutschland GmbH, 2024)
This chapter examines the influence of Accounting Information Systems (AIS) on organizational resilience. Anchored in a positivist framework and using a deductive methodology, this empirical research utilizes the SEM-ANN Approach to investigate the effects of AIS-related Human Competency, Complementary Business Intelligence System, and Flexible AIS on organizational resilience. The study is based on a sample from large Malaysian organizations listed on the Bursa Malaysia stock exchange, selected for their rich data availability and high level of engagement with dynamic AIS systems. Key outcomes indicate that all three variables significantly impact organizational resilience. Of these, Flexible AIS stands out as the most influential, followed by the Complementary Business Intelligence System and AIS-related Human Competency. The research emphasizes the vital role that AIS plays in fortifying organizational resilience and provides valuable insights for professionals aiming to use AIS for sustaining organizational effectiveness. Future research avenues include examining possible moderating factors and conducting detailed analyses of the sub-dimensions of each contributing factor, thereby adding more nuance to our understanding of AIS's role in organizational resilience. As such, this study acts as a foundational piece for further research into how AIS impacts organizational resilience across various settings and temporal dimensions. The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.